DISTRIBUSI DANA ZAKAT GUNA PEMBERDAYAAN MASYARAKAT OLEH LAZISNU DUKUHTURI DALAM PANDANGAN MAJELIS ULAMA INDONESIA KABUPATEN TEGAL - Tubagus Firdos; Mubarok (el hisbah: Journal of Islamic Economic Law, 2022)
This study examines the Distribution of Zakat Funds for Community Empowerment in the View of the Indonesian Ulema Council of Tegal Regency. Distribution of ZIS funds given to mustahiq as capital to carry out an economic activity, namely to meet basic needs and to develop the economic level and productivity potential of mustahiq. At LAZISNU Dukuhturi, many people have been given consumptive and productive zakat, there are still many who only care about consumptive zakat and do not know what the law is for productive zakat itself. The results obtained indicate that this study aims to determine and analyze the views of the MUI of Tegal Regency on the distribution of ZIS funds for community empowerment. The distribution of ZIS funds carried out by LAZISNU dukuhturi in the view of the Tegal Regency MUI is allowed. However, there needs to be an increase that must be expanded in its distribution so that the community, especially the Dukuhturi District, feels.